The presidential appointee's handbook - DeSeve, G. Edward (Washington, D.C Brookings Institution Press, 2017)
The transition from one president to another, regardless of which party wins the 2016 elections, will mean many things, one of which is that some 3,000 to 4,000 new senior presidential appointees will take office in the first months of 2017. They will join some 6,000 members of the Senior Executive Service and nearly 1,000 admirals and generals already working in the top ranks of government.
Includes bibliographical references (pages 165-174) and index.
Keywords: Cabinet officers--Selection and appointment--United States